Methacrylate Copolymers with Liquid Crystalline Side Chains for Organic Gate Dielectric Applications - Berndt, Andreas; Pospiech, Doris; Jehnichen, Dieter; Haeussler, Liane; Voit, Brigitte; Al-Hussein, Mahmoud; Ploetner, Matthias; Kumar, Amit; Fischer, Wolf-Joachim (ACS Applied Materials and Interfaces, 2015)
Polymers for all-organic field-effect transistors are under development to cope with the increasing demand for novel materials for organic electronics. Besides the semiconductor, the dielectric layer determines the efficiency of the final device. Poly(methyl methacrylate) (PMMA) is a frequently used dielectric. In this work, the chemical structure of this material was stepwise altered by incorporation of cross-linkable and/or self-organizing comonomers to improve the chemical stability and the dielectric properties. Different types of cross-linking methods were used to prevent dissolution, swelling or intermixing of the dielectric e.g. during formation processes of top electrodes or semiconducting layers. Self-organizing comonomers were expected to influence the dielectric/semiconductor interface, and moreover, to enhance the chemical resistance of the dielectric. Random copolymers were obtained by free radical and reversible addition-fragmentation chain transfer (RAFT) polymerization. With 6-[4-(4′-cyanophenyl)phenoxy]alkyl side chains having hexyl or octyl spacer, thermotropic liquid crystalline (LC) behavior and nanophase separation into smectic layers was observed, while copolymerization with methyl methacrylate induced molecular disorder. In addition to chemical, thermal and structural properties, electrical characteristics like breakdown field strength (EBD) and relative permittivity (k) were determined. The dielectric films were studied in metal-insulator-metal setups. EBD appeared to be strongly dependent on the type of electrode used and especially the ink formulation. Cross-linking of PMMA yielded an increase in EBD up to 4.0 MV/cm with Ag and 5.7 MV/cm with PEDOT:PSS electrodes because of the increased solvent resistance. The LC side chains reduce the ability for cross-linking resulting in decreased breakdown field strengths.
CRIS-Team Scopus Importer:2023-03-20
Keywords: breakdown field strength; dielectric layer; liquid crystalline side chain polymers; methacrylate copolymers; relative permittivity